Contemporary Issues of Multicultural-Based Islamic Education: Obstacles and Development Strategies - Aini Fahrunisa; Fery Diantoro; Erlinda Purbaningrum; Siti Hayu Maimunah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This research aims to examine contemporary issues that become obstacles in the implementation of multicultural-based Islamic education and formulate its development strategies in the digital era. This research uses a qualitative approach with the literature study method, namely analysing various journals and relevant scientific sources without directly involving field samples. The research results show that there are several main obstacles, namely the gap between the ideal values of Islamic teachings and learning practises, the emergence of religious exclusivity, the influence of radicalism and intolerance, and the impact of uncontrolled digital information flow such as the echo chamber phenomenon. In addition, the curriculum that is still cognitively oriented and the limited competence of teachers in applying a multicultural approach also strengthens the problem. Social environment factors also affect the formation of students' mindsets in addressing diversity. Therefore, a comprehensive development strategy is needed, including strengthening the multicultural-based curriculum, implementing dialogue learning, improving digital literacy, developing teacher competence, and creating an inclusive education environment. This research recommends that Islamic education should be more adaptive, contextual, and integrative in facing the challenges of the digital era in order to form students who are inclusive, tolerant, and able to live harmoniously in a multicultural society.